(untitled) (Oratio Directa, 2021)
This study examines the application of literary journalism in John Hersey's Hiroshima. It uses a qualitative descriptive approach with the book as the unit of analysis. The analysis applies Robert Vare's seven considerations for literary journalism: facts, conflict, character, access, emotion, time travel, and novelty. The findings show that Hiroshima is grounded in the historical event of the atomic bombing and in first-hand accounts from six survivors. Conflict is developed through the immediate destruction and the survivors' continuing physical and social consequences. Distinct characters, direct reporting access, emotional detail, and an interwoven chronology give the report narrative depth. Its novelty lies in presenting the catastrophe through the everyday experiences of civilians rather than through military or state perspectives. The seven elements operate as an integrated narrative strategy, supporting the classification of Hiroshima as literary journalism.